1994
DOI: 10.2105/ajph.84.3.459
|View full text |Cite
|
Sign up to set email alerts
|

The weights and heights of Mexican-American adolescents: the accuracy of self-reports.

Abstract: The accuracy of Mexican-American adolescents' self-reported weights, heights, and body mass indexes was evaluated with data from the Hispanic Health and Nutrition Examination Survey. On average, adolescents with low measured body mass indexes and high measured body mass indexes overestimated and underestimated their weights, respectively. Categories of low and high body mass indexes created by applying cutoffs to reported body mass indexes had low sensitivities. For weight, height, and body mass indexes, measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
3
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 15 publications
(1 reference statement)
8
55
3
4
Order By: Relevance
“…Therefore, we tested whether self-reported weight status categories during childhood and adolescence were useful in predicting metabolic risk factors among Mexican young adults. There is evidence of the validity of self-reported weight and body perception to estimate current weight in among Mexican adolescents and adults [16,17]. However, we found little evidence that weight change patterns based on recalled weight status during childhood and adolescence contributed to the prediction of metabolic risk at young adulthood.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Therefore, we tested whether self-reported weight status categories during childhood and adolescence were useful in predicting metabolic risk factors among Mexican young adults. There is evidence of the validity of self-reported weight and body perception to estimate current weight in among Mexican adolescents and adults [16,17]. However, we found little evidence that weight change patterns based on recalled weight status during childhood and adolescence contributed to the prediction of metabolic risk at young adulthood.…”
Section: Discussioncontrasting
confidence: 70%
“…Therefore, alternative options such as the use of self-reported retrospective information on weight status have been used in large scale studies. For instance, previous studies have assessed the accuracy of self-reported weight among Mexican Adolescents, and also self-reported body mass index (BMI) and body perception among Mexican adults; their findings suggested that self-reported weight among these populations are highly correlated with the measured BMI and thus may be valid to estimate weight in epidemiological studies [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown a high validity of self-reported BMI in older children and adolescents (Tienboon et al, 1992;Davis & Gergen, 1994;Strauss, 1999;Kuczmarski et al, 2000;Himes & Faricy, 2001). Prevalence of obesity in Greek children and adolescents D Karayiannis et al Goodman et al (2000) reported that 96% of adolescents correctly classified their obesity status based on self-reported data, and they concluded that self-reported height and weight could be used to accurately evaluate older children's and teens' obesity risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that reported data have high specificity (92%-99%). However, the sensitivity of self-reported data to detect obesity has ranged from 45% to 76% [19,32,33]. This low sensitivity likely accounts for the lower prevalence of obesity that we observed compared with NHANES.…”
mentioning
confidence: 63%
“…Second, the sample child's weight and height used to calculate BMI were reported by an adult respondent, typically a parent. Despite the high correlations between measured and parent-reported weight, height, and BMI among adolescents, mean weight is typically underestimated from reported data, with a larger difference between reported and measured data for female than male adolescents [19,[31][32][33][34]. Some studies demonstrated that reported data have high specificity (92%-99%).…”
mentioning
confidence: 99%